2019
DOI: 10.1007/s10853-019-03854-5
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of fibrous carbon materials

Abstract: The air permeability of a number of commercial fibrous carbon materials: soft non-woven felts, rigidized felts and rigid boards, based on either PAN-or Rayon-derived fibres presenting various diameters, graphitised or not, and consolidated by different methods, was measured and investigated. Consistent behaviours were found within families of closely related materials, but the diversity of porous structures prevented any model, including the very popular Tomadakis-Sotirchos equation, to fit all results. The Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
(111 reference statements)
1
14
0
Order By: Relevance
“…In addition to differences in manufacturing processes and precursors [31], CFs also differ in terms of carbon and heteroelement contents. The performance of the analysis showed that the elemental composition of commercial CFs is highly repeatable, with maximal standard deviations of 0.45 wt % for C and O, or 0.01 wt % for the other heteroatoms.…”
Section: Cfs Elemental Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to differences in manufacturing processes and precursors [31], CFs also differ in terms of carbon and heteroelement contents. The performance of the analysis showed that the elemental composition of commercial CFs is highly repeatable, with maximal standard deviations of 0.45 wt % for C and O, or 0.01 wt % for the other heteroatoms.…”
Section: Cfs Elemental Compositionmentioning
confidence: 99%
“…SEM micrographs of the carbon fibre morphology of de-sized materials before and after reaction in molten LiOH are shown in Figures 11 and 12 for ex-Rayon CFs and ex-PAN CFs, respectively. As detailed in a former study from our group [31], the morphology of the outer surface and the cross-section of de-sized carbon fibres prior to reaction varies with the precursor and the manufacturing technology, since these commercial materials come from different suppliers.…”
Section: Chemical Stability Of Cfs In Lioh With Regard To Their Morphmentioning
confidence: 99%
“…Samples of 18 commercial fibrous carbons (see Table S1 of Supplementary Material ) were used here for the evaluation of their mechanical and thermal properties. In our previous studies [ 21 , 26 ], where the same materials have been studied for other properties and applications, we have already given the general characteristics of these materials, especially how they are manufactured, and how the precursor of the fibers and/or the production history can affect their structural and morphological properties at the micro/macro scale. It is particularly important to remember here that we are dealing with flexible CFs on the one hand, rigidized CFs on the other, and also rigid fibrous panels, and that their constituent fibers are either PAN-based (with two qualities: thin and thick fibers) or Rayon-based.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, all these materials were either carbonized or graphitized, depending on the heat treatment temperature seen by the fibers during their manufacturing process. Based on this general data, all materials were classified into groups and sub-groups, as justified in the first paper of this series [ 26 ]. This information, together with the names of suppliers, the trade names of the materials and the reference codes used in this work are given in Table S1 of the Supplementary Material .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation